Planothidium krascheninnikovii sp. nov. (Achnanthidiaceae, Bacillariophyceae)—a new large-celled monoraphid species from freshwater environments of the Kamchatka Peninsula, Russia - Glushchenko, Anton; Tseplik, Natalia; Kulikovskiy, Maxim (Phytotaxa, 2026)
As a result of a study of freshwater diatom flora in Kamchatka, a new species of the genus Planothidium was found: Planothidium krascheninnikovii sp. nov. The species was studied using light and scanning electron microscopy. A comparison was made with morphologically similar species, Planothidium lanceolatoides and P. cyclophorum. The new species is distinguished by strongly silicified valves and the presence of sickle-shaped protrusions at the junction between valve face and mantle of the rapheless valve. The article also presents the history of studies of monoraphid diatoms from the aquatic ecosystems in the Kamchatka Peninsula.